IMPLEMENTASI METODE WEBQUAL DAN CUSTOMER SATISFACTION INDEX UNTUK MENGEVALUASI WEBSITE PERGURUAN TINGGI NEGERI DI BANDAR LAMPUNG - Tristiyanto Tristiyanto; Deviana Saputri; Muhammad Iqbal (Lambung Mangkurat University, 2020)
This study provides an overview of the quality of six state University website services in Bandar Lampung which refered to three dimensions, website usability, information quality, and interaction quality website. This study also used the Customer Satisfaction Index (CSI) method to determine the level of user satisfaction. In addition, to improve the usability of a website, website performance testing was performed using automatic tools. The result of this research find that the quality of website services is influenced by the content on the website. The result of CSI analysis on the website of state Universities in Bandar Lampung are satisfied with the website service at each state University in Bandar Lampung. Based on the results of the usability evaluation using automatic tools on the website, it is known that the website of state Universities in Bandar Lampung is good enough as evidenced by the page load time value which was less the three seconds.Keywords: Quality of Website Service, WebQual, CSI, UsabilityPenelitian ini mengkaji kualitas layanan pada enam website universitas negeri di Bandar Lampung dengan menggunakan metode Webqual yang merujuk pada 3 hal yaitu – website usability, kualitas informasi dan kualitas interaksi website. Kepuasan pengguna diukur menggunakan metode Customer Satisfaction Index (CSI). Untuk meningkatkan website usability dilakukan website performance tes menggunakan alat otomatis. Hasil dari penelitian ini memperlihatkan kualitas layanan website dipengaruhi oleh konten website. Sedangkan hasil Analisa CSI pada website universitas negeri di Bandar Lampung adalah memuaskan untuk setiap website universitas tersebut. Berdasarkan hasil evaluasi usability, website universitas negri di Bandar Lampung menunjukkan sudah cukup baik dengan waktu load halaman kurang dari tiga detik.Kata Kunci: Kualitas Layanan Website, WebQual, CSI, Usability